2015
DOI: 10.1007/s00246-015-1100-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Catheterization in Children with Pulmonary Hypertensive Vascular Disease

Abstract: The risks associated with cardiac catheterization in children with pulmonary hypertension (PH) are increased compared with adults. We reviewed retrospectively all clinical data in children with PH [mean pulmonary artery pressure (mean PAp) ≥25 mmHg and pulmonary vascular resistance index (PVRI) ≥3 Wood units m(2)] undergoing cardiac catheterization between 2009 and 2014. Our strategy included a team approach, minimal catheter manipulation and sildenafil administration prior to extubation. Adverse events occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…However, the proper timing of cardiac catheterization is often less clear, in part because the risks increase in patients with acute disease. In fact, a recent study found that the risks of cardiac catheterization are higher in pediatric patients with PH compared to adults, but that it can be performed safely in these patients when undertaken with a programmatic approach (10). …”
Section: Diagnosismentioning
confidence: 99%
“…However, the proper timing of cardiac catheterization is often less clear, in part because the risks increase in patients with acute disease. In fact, a recent study found that the risks of cardiac catheterization are higher in pediatric patients with PH compared to adults, but that it can be performed safely in these patients when undertaken with a programmatic approach (10). …”
Section: Diagnosismentioning
confidence: 99%
“…[2022] The occurrence of AF in patients with uncorrected ASD is estimated to be 20%, and the prevalence of atrial arrhythmia increases with age and mean pulmonary arterial pressure. [7,17,20,21] Long-standing volume overload due to left-to-right shunts causes enlargement of the right atrium. Even many years after correction, this may result in conduction disturbances in the atrial myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Trans-catheter closure was performed by 2 pediatricians who specialized in interventional procedures. All procedures were performed with the Amplatzer Septal Occluder (ASO, AGA Medical, Golden Valley, MN).…”
Section: Methodsmentioning
confidence: 99%
“…In the series from Bobhate, Zuckerman, and Beghetti(24) the 95% confidence intervals for observed risk of mortality are 0–3.7%, 0.2–1.0%, and 0.2–1.3%. The standardized risk of composite outcome in our study was slightly higher (3.3%, 95% CI: 1.9–5.5%).…”
mentioning
confidence: 99%